Implementasi Peraturan Lingkungan Bagi Masayarakat Desa Suka Maju (Sosialisasi UU No. 32 Tahun 2009 Tentang Lingkungan Hidup) - Elyani, Elyani; Darma, Mospa; Rismayanti, Rismayanti; Azhar, Ade Wahyudi; Zega, Yamolala; Waruwu, Khamo; Tanjung, Oppie Meisya (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut Nyak Dhien, 2025)
A clean and healthy environment is a fundamental need for a dignified community life. However, Suka Maju Village continues to face various environmental issues, such as illegal waste accumulation and low public awareness of cleanliness. This study aims to increase public awareness regarding the importance of environmental hygiene and to encourage the formulation of Village Regulations (Peraturan Desa or Perdes) as a form of support for the implementation of Law of the Republic of Indonesia Number 32 of 2009 on Environmental Protection and Management, particularly Chapter V Article 13. The method used was a community service approach through the Student Creativity Program (Program Kreativitas Mahasiswa or PKM), which involved socialization activities, educational outreach, and facilitated group discussions with village officials and residents. The results indicate a significant increase in community awareness of environmental cleanliness, along with an initiative by the village administration to draft a Perdes on clean living practices. This activity also strengthened collaboration between local authorities, students, and the community in promoting a healthy and sustainable environment. In conclusion, a participatory approach to implementing environmental regulations at the village level proves effective in driving behavioral change and supporting the concrete realization of environmental law objectives at the grassroots level.